Techniques and strategies for hand rejuvenation: an up-to-date review - Scevola, Silvia; Soldà, Nicola Luigi; Arpino, Aldo; Saler, Marco; Faga, Angela; Nicoletti, Giovanni (Aesthetic Medicine, 2026)
Introduction: Hands significantly contribute to an individual’s aesthetic appearance and can be indicative of a person’s age even more than their face. Despite their significant social and aesthetic impact, hands have traditionally received less attention in cosmetic treatments compared to the face and neck. In recent years, Aesthetic Medicine has shown growing interest in hand rejuvenation techniques. Objectives: This review explores the literature reports on the main techniques employed in hand rejuvenation. Methods: PubMed–indexed articles were searched using the keywords: "hand rejuvenation", "hand aging", "dermal filler", "chemical peel", "laser", "sclerotherapy", and "fat grafting" in different combinations. All references cited in the selected articles were examined to identify additional relevant sources. Only studies involving patients treated specifically for hand rejuvenation were included. Articles lacking objective outcome data or focusing on techniques without clinical validation were excluded. Results: A total of 78 articles (14 reviews and 64 original articles) were retrieved, spanning from the year 2000 to 2025 and published in 21 countries. Twenty-two single treatments and seven combination protocols were identified. Conclusions: Available evidence supports the safety and efficacy of both single and combined approaches for hand rejuvenation, emphasizing the need for individualized, anatomy-based treatment planning to optimize outcomes.